Theory of planned behavior in creating disease prevention behavior - Prasetya, Hanung; Darmayanti, Aquartuti Tri; Setyorini, Yuyun (Intelektual Pustaka Media Utama, 2024)
Human behavior, in dealing with pandemic, becomes one of the key factors during the speed of an outbreak. In this way, individual and social responsibility are needed to determine behaviors, end the pandemic, and anticipate for the next outbreak. The purpose of this systematic review is to provide structured information about the results of applying the theory of planned behavior (TPB) in concern to create COVID-19 preventive behavior (CPB) as the case example. This systematic review was compiled by searching articles using the keywords